2023
DOI: 10.1161/hypertensionaha.122.17947
|View full text |Cite
|
Sign up to set email alerts
|

Established and Emerging Cancer Therapies and Cardiovascular System: Focus on Hypertension—Mechanisms and Mitigation

Abstract: Cardiovascular disease and cancer are 2 of the leading causes of death worldwide. Although improvements in outcomes have been noted for both disease entities, the success of cancer therapies has come at the cost of at times very impactful adverse events such as cardiovascular events. Hypertension has been noted as both, a side effect as well as a risk factor for the cardiotoxicity of cancer therapies. Some of these dynamics are in keeping with the role of hypertension as a cardiovascular risk factor not only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 331 publications
0
2
0
Order By: Relevance
“…Previous research has found a correlation between cancer and CVD. [26][27][28] A large nationwide study found a greater risk of CVD death in patients with cancer compared with the general population. 26 The Atherosclerosis Risk in Communities study also found that cancer survivors with atherosclerosis risk have significantly higher risk of CVD independent of traditional cardiovascular risk factors.…”
Section: Cancer Survivors and Cardiovascular Outcomesmentioning
confidence: 99%
“…Previous research has found a correlation between cancer and CVD. [26][27][28] A large nationwide study found a greater risk of CVD death in patients with cancer compared with the general population. 26 The Atherosclerosis Risk in Communities study also found that cancer survivors with atherosclerosis risk have significantly higher risk of CVD independent of traditional cardiovascular risk factors.…”
Section: Cancer Survivors and Cardiovascular Outcomesmentioning
confidence: 99%
“…Although it may serve as a marker of antiangiogenic action and treatment efficacy, S1 severe hypertension can contribute to cardiovascular morbidity and mortality, leading to interruption or discontinuation of VSPIs. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria can also occur with VSPI therapy in 21% to 63% of treated patients, 5 and is thought to occur via rarefaction of the peritubular capillary network and disruption of the paracrine signaling between the podocyte and glomerular endothelium. Like VSPI-associated hypertension, proteinuria is associated with cardiovascular disease and poor patient outcomes, necessitating frequent monitoring after starting VSPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their treatments are frequently influenced by drugs against common diseases, for instance, drugs against infection, cardiovascular disease, respiratory system disease, and nausea. 10 , 11 CYP-based drug-drug interaction (DDI) is common in clinical practice. Therefore, evaluating pharmacokinetic DDI, especially CYP3A4 involved metabolic interaction is essential to ensure safety in cancer patients.…”
Section: Introductionmentioning
confidence: 99%